NR2B Gene Expression Change in Wistar Rat Practicing Aerobic Exercise Comparing to Soybean (Glycine max) or Phyllanthus niruri Intakes and Soybean and Phyllanthus niruri Composition Intake - Vita Muniarti Tarawan; Diah Dhianawaty; Tetty Yuniati; Muhamad Nurhalim Shahib (International Journal of Integrated Health Sciences, 2015)
Objective: The objective of this study is to examine the relation between nutrition and brain memory. Qualified human resource is the most valuable national asset. Adequate nutrition and regular exercise provide higher achievement to create healthy and smart generations.Methods: The method applied in this study was experimental laboratory. This study was conducted on Juni 2011–Juli 2012 at the Biomedical and Biochemistry laboratory, Faculty of Medicine, Universitas Padjadjaran. The subjects were 8 weeks approximately 200–250 grams, male Wistar rats. The examination involved 56 male Wistar rats divided into 8 groups with different treatments. The groups which received exercise treatment were also given Glycine max and Phyllanthus niruri intakes. Results: NR2B gene expression changes can be described as the following results: (1) without practicing exercise (3,8) and after exercises (4,6); (2) Glycine max intake minus exercise (2,86) and Glycine max intake and exercises (3,17); (3) Phyllanthus niruri intake minus exercises (4,7) and Phyllanthus niruri intake and exercises (4,9); and (4) Glycine max and Phyllanthus niruri composition intake minus exercises (3,14) and Glycine max and Phyllanthus niruri composition intake and exercises (4,83).Conclusions: This study determines that exercises and Phyllanthus niruri intake enhance NR2B gene expressions. Glycine max inhibits the NR2B gene expressions. Glycine max and Phyllanthus niruri composition intake and either with or without practicing exercises enhance NR2B gene expressions. Therefore, practicing exercises and Phyllanthus niruri intake might cause brain cell apoptosis while Glycine max intake inhibits brain cell apoptosis. Keywords: Exercise, gene expressions, Glycin max, NR2B, Phyllanthus niruri DOI: 10.15850/ijihs.v3n2.582